2020
DOI: 10.21595/vp.2020.21603
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of shear-tension spring-type quasi-zero stiffness isolator

Abstract: By connecting the linear compression spring (positive stiffness mechanism) in parallel with the tension spring (negative stiffness mechanism) and using the shear lever mechanism to amplify the motion of the negative stiffness mechanism, a shear-tension spring type quasi-zero stiffness isolation system is constructed, which is suitable for low-frequency and ultra-low-frequency vibration isolation, especially for small-amplitude, low-frequency vibration isolation. In addition, the vibration isolation system has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Cheng et al found that the changes in load and excitation amplitude had impacts on vibration control performance [19]. A quasi-zero stiffness vibration isolator based on a shear lever mechanism was presented in [20], which cannot only guarantee the function of quasi-zero stiffness, but also has an adjustable capacity to adapt to a variation of load. A cam-roller vibration control system based on a quasi-zero stiffness mechanism was proposed in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al found that the changes in load and excitation amplitude had impacts on vibration control performance [19]. A quasi-zero stiffness vibration isolator based on a shear lever mechanism was presented in [20], which cannot only guarantee the function of quasi-zero stiffness, but also has an adjustable capacity to adapt to a variation of load. A cam-roller vibration control system based on a quasi-zero stiffness mechanism was proposed in [21].…”
Section: Introductionmentioning
confidence: 99%